FMS Mutations in Myelodysplastic, Leukemic, and Normal Subjects - Ridge, Susan A.; Worwood, Mark; Oscier, David; Jacobs, Allan; Padua, Rose Ann (Proceedings of the National Academy of Sciences - PNAS, 1990)
The FMS gene encodes the functional cell surface receptor for colony-stimulating factor 1, the macrophage- and monocyte-specific growth factor. Codons 969 and 301 have been identified as potentially involved in promoting the transforming activity of FMS. Mutations at codon 301 are believed to lead to neoplastic transformation by ligand independence and constitutive tyrosine kinase activity of the receptor. The tyrosine residue at codon 969 has been shown to be involved in a negative regulatory activity, which is disrupted by amino acid substitutions. This study reports on the frequency of point mutations at these codons, in vivo, in human myeloid malignancies and in normal subjects. We studied 110 patients [67 with myelodysplasia (MDS) and 48 with acute myeloblastic leukemia (AML)], 5 patients being studied at the MDS and the later AML stage of the disease. There was a total incidence of 12.7% (14/110) with mutations in codon 969 and 1.8% (2/110) with mutations in codon 301. Two patients had mutations in the AML stage of the disease but not in the preceding MDS and one had a mutation in the MDS stage but not upon transformation of AML. This is consistent with the somatic origin of these mutations. FMS mutations were most prevalent (20%) in chronic myelomonocytic leukemia and AML type M4 (23%), both of which are characterized by monocytic differentiation. One of 51 normal subjects had a constitutional codon 969 mutation, which may represent a marker for predisposition to myeloid malignancy.